Is the Learning Organization for Real? Examining the Impacts of the Dimensions of the Learning Organization on Organizational Performance - Andrea D. Ellinger; Baiyin Yang; Alexander E. Ellinger (Adult Education Research Conference, 2000)
Despite the controversial nature of the learning organization concept, few empirical studies have examined the relationship between the learning organization concept and firm performance. An exploratory study was conducted using the DLOQ© along with objective measures of firm financial performance to assess this association. Findings suggest positive associations between the learning organization concept and firm performance.